2021
DOI: 10.3390/ijms22094653
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Small Extracellular Vesicles from Human Sera

Abstract: Robust, well-characterized methods for purifying small extracellular vesicles (sEV) from blood are needed before their potential as disease biomarkers can be realized. Here, we compared isolation of sEV from serum by differential ultracentrifugation (DUC) and by exclusion chromatography using commercially available Exo-spin™ columns. We show that sEV can be purified by both methods but Exo-spin™ columns contain copious additional particles recorded by nanoparticle tracking analysis, invalidating its use for qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Little is known about the functions of CD62p+ exosomes in severe injury. These exosomes were shown to be released from endothelial cells, but also from platelets and megakaryocytes ( 31 ). Experimental studies in vivo and in vitro have shown that the release of particles from endothelial cells can be caused by chest trauma or as a result of endothelial cell incubation with a polytrauma cytokine cocktail ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the functions of CD62p+ exosomes in severe injury. These exosomes were shown to be released from endothelial cells, but also from platelets and megakaryocytes ( 31 ). Experimental studies in vivo and in vitro have shown that the release of particles from endothelial cells can be caused by chest trauma or as a result of endothelial cell incubation with a polytrauma cytokine cocktail ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the CD81 abundance was similar in all three sample types. The sEV purified by Exo-spin gave qualitatively similar results, albeit with lower abundance, reflecting the paucity of sEV obtained by this method (Figure 1b, d) (Małys et al, 2021). Indeed, CD9 and CD63 were only detectable in serum-derived sEV and CD81 was uniformly low (Figure 1d).…”
Section:  Differences Between Sev Preparations From Various Sample ...mentioning
confidence: 72%
“…Afterwards, the sEV pellet was collected into an Eppendorf tube, in which the volume was adjusted to a total of 200 μL by addition of cold PBS and down-stream analysis was performed immediately or within the next hours of 4 • C storage. This method was previously validated by us showing purity and quality of the sEV preparations according to MISEV standards (Małys et al, 2021;Théry et al, 2018).…”
Section:  Isolation Of Sev By Differential Ultracentrifugationmentioning
confidence: 99%
“…The presence of TSG101, CD81, and CD9 on the MV surface was determined by Western blotting [ 44 46 ]. The protein concentration was measured using the BCA assay following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%